2017
DOI: 10.1016/j.chom.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Segmented Filamentous Bacteria Provoke Lung Autoimmunity by Inducing Gut-Lung Axis Th17 Cells Expressing Dual TCRs

Abstract: SUMMARY Lung complications are a major cause of rheumatoid arthritis-related mortality. Involvement of gut microbiota in lung diseases by the gut-lung axis has been widely observed, but the underlying mechanism remains mostly unknown. Using an autoimmune arthritis model, we show that a constituent of the gut microbiota, segmented filamentous bacteria (SFB), distantly provoke lung pathology. SFB induce autoantibodies in lung during the pre-arthritic phase, and SFB-dependent lung pathology requires the T helper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(121 citation statements)
references
References 46 publications
3
117
0
1
Order By: Relevance
“…We anticipate that there are additional factors and immune cell networks downstream of CX3CR1 + MNPs that may contribute to the effect of gut fungal dysbiosis on AAD. A recent study has indeed demonstrated that lung autoimmune inflammation can be triggered by segmented filamentous bacteria gut-lung axis Th17 cell induction (Bradley et al, 2017). While our study exploring the innate immune events affecting lung allergy during gut fungal dysbiosis, it will be important for future studies to determine how adaptive antifungal responses generated upon CX3CR1 + MNP activation affect systemic and distal site immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We anticipate that there are additional factors and immune cell networks downstream of CX3CR1 + MNPs that may contribute to the effect of gut fungal dysbiosis on AAD. A recent study has indeed demonstrated that lung autoimmune inflammation can be triggered by segmented filamentous bacteria gut-lung axis Th17 cell induction (Bradley et al, 2017). While our study exploring the innate immune events affecting lung allergy during gut fungal dysbiosis, it will be important for future studies to determine how adaptive antifungal responses generated upon CX3CR1 + MNP activation affect systemic and distal site immunity.…”
Section: Discussionmentioning
confidence: 99%
“…While our study exploring the innate immune events affecting lung allergy during gut fungal dysbiosis, it will be important for future studies to determine how adaptive antifungal responses generated upon CX3CR1 + MNP activation affect systemic and distal site immunity. Gut–lung axis migration of T cells, innate lymphoid cells or inflammation-related factors have been shown to occur (Bradley et al, 2017; Huang et al, 2018; Kim et al, 2014) and could be possible avenues to pursue in future studies investigating the role of fungal dysbiosis on peripheral immunity and inflammatory diseases at gut distal sites.…”
Section: Discussionmentioning
confidence: 99%
“…SFB‐specific Th17 cells are found in the peripheral lymphoid organs beyond the intestine, which could potentially contribute to the vulnerability to some autoimmune diseases in genetically susceptible hosts . In addition to previously proposed molecular mimicry and bystander activation theories as to the mechanism for microbiota‐reactive T cells to trigger autoimmunity, a recent study in a lung autoimmune mouse model showed that SFB selectively expanded Th17 cells that expressed dual TCR, one of which recognized SFB peptide and the other directed at a self‐antigen …”
Section: T Cell–gut Microbiota Interactionsmentioning
confidence: 99%
“…There is also growing evidence that gut-lung axis and gut microbiota induced inflammation may lead to the development of chronic inflammatory disorders of the respiratory as well as GI tract [111]. It has been demonstrated that autoimmunity of the lungs can be driven by Th17 cells that are induced by SFB in the gut by promoting inducible bronchus associated lymphoid tissues, a type of ectopic lymphoid tissues in the lung of rheumatoid arthritis patients [112]. Therefore, manipulating the gut microbiota may also be useful in the treatment of respiratory diseases.…”
Section: The Respiratory Microbiome-asthma and Respiratory Diseasesmentioning
confidence: 99%